2008
DOI: 10.1021/nl803174p
|View full text |Cite
|
Sign up to set email alerts
|

A Bicontinuous Double Gyroid Hybrid Solar Cell

Abstract: We report the first successful application of an ordered bicontinuous gyroid semiconducting network in a hybrid bulk heterojunction solar cell. The freestanding gyroid network is fabricated by electrochemical deposition into the 10 nm wide voided channels of a self-assembled, selectively degradable block copolymer film. The highly ordered pore structure is ideal for uniform infiltration of an organic hole transporting material, and solid-state dye-sensitized solar cells only 400 nm thick exhibit up to 1.7% pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
503
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 480 publications
(509 citation statements)
references
References 36 publications
6
503
0
Order By: Relevance
“…Recently, gyroid and columnar structures were replicated in anatase titania and the titania structures immersed in dye and back filled with a liquid electrolyte to create dye-sensitised cells (DSCs). 26,27 These cells show power efficiencies of around 2%, considerably less than the best efficiencies of 11% obtained for liquid electrolyte dye-sensitised cells made from mesoporous titania, 28 but comparable to devices of a similar thickness. To the authors' knowledge, such bicontinuous structures have yet to be adopted in an all-conjugated polymer solar cell, although diblock copolymers based on conjugated polymers have now been synthesised.…”
Section: Introductionmentioning
confidence: 79%
“…Recently, gyroid and columnar structures were replicated in anatase titania and the titania structures immersed in dye and back filled with a liquid electrolyte to create dye-sensitised cells (DSCs). 26,27 These cells show power efficiencies of around 2%, considerably less than the best efficiencies of 11% obtained for liquid electrolyte dye-sensitised cells made from mesoporous titania, 28 but comparable to devices of a similar thickness. To the authors' knowledge, such bicontinuous structures have yet to be adopted in an all-conjugated polymer solar cell, although diblock copolymers based on conjugated polymers have now been synthesised.…”
Section: Introductionmentioning
confidence: 79%
“…41 The use of an inorganic semiconductor as acceptor allows the construction of a rigid nanostructured acceptor phase, e.g. by solution based techniques, and the subsequent infilling of the pores of the inorganic film with an organic donor component.…”
Section: Alternative Strategies To Control the Microstructure Of Donomentioning
confidence: 99%
“…[ 9 ] Some studies have shown that 3D architectures outperform those of lower dimensionality (e.g., nanowire arrays) in terms of their mechanical stability. [ 10,11 ] Additionally, 3D interconnectivity guarantees the transport of charge carriers across the network. remaining phase.…”
Section: Introductionmentioning
confidence: 99%